Adoption of the Creative Process According to the Immersive Method - Sonja Vuk; Tonka Tacol; Janez Vogrinc (Center for Educational Policy Studies Journal)
The immersive method is a new concept of visual education that is better suited to the needs of students in contemporary post-industrial society. The features of the immersive method are: 1) it emerges from interaction with visual culture; 2) it encourages understanding of contemporary art (as an integral part of visual culture); and 3) it implements the strategies and processes of the dominant tendencies in contemporary art (new media art and relational art) with the goal of adopting the creative process, expressing one’s thoughts and emotions, and communicating with the environment. The immersive method transfers the creative process from art to the process of creation by the students themselves. This occurs with the mediation of an algorithmic scheme that enables students to adopt ways to solve problems, to express thoughts and emotions, to develop ideas and to transfer these ideas to form, medium and material. The immersive method uses transfer in classes, the therapeutic aspect of art and “flow state” (the optimal experience of being immersed in an activity)/aesthetic experience (a total experience that has a beginning, a process and a conclusion)/immersive experience (comprehensive immersion in the present moment). This is a state leading to the sublimative effect of creation (identification with what has been expressed), as well as to self-actualisation. The immersive method teaches one to connect the context, social relations and the artwork as a whole in which  one lives as an individual. The adopted creative process is implemented in a critical manner on one’s surrounding through analysis, aesthetic interventions, and ecologically and socially aware inclusion in the life of a community. The students gain the crucial meta-competence of a creative thinking process.